Analysis of The Causes of Factors and Types of Injuries In Football Game and Its Impact On The Psychic Condition of Athletes - Satni Ginting; Noortje Anita Kumaat (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The results showed 1) there are two factors causing injury in soccer games, namely internal and external. However, from these two factors internal factors are the main causes of injuries suffered by football atheles. The factors that cause internal injury in question are the wrong technique performed by the athlete. As for the second factor, namely external causes due to the facilities used by athletes. 2) the types of injuries that occur most frequently in this study are the first hip injury, the second knee injury, the third wrist injury, the fourth ankle injury, the fifth elbow injury and the last one is the shoulder injury. 3) the psychological impact most often felt by athletes when experiencing an injury is the first is the psychlogical impact of feeling sad (grief), the second is the symptoms of depression and irritability and last is the psychological impact of separation